Acute Nitrate Poisoning in Goats - Issi, Mustafa; Gul, Yusuf; Ilhan, Selcuk; Basbug, Onur; Gul, Burcu (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
The aim of this study was to analyze clinical, hematological and some biochemical parameters in 7 hair goats aged 1-2 which accidentally ingested nitrate fertilizer and to evaluate the necropsy findings in 2 mandatorily slaughtered goats. According to the clinic and necropsy findings, anamnesis information and blood spot tests, methylene blue (1%, 20 mg/kg, IV) and ascorbic acid (10 mg/kg dose IV) were used in the treatment of the animals suspected for nitrate poisonings. Absolute diagnosis was got considering the determination of nitrite level in blood serum and getting positive answers to the treatment. In conclusion, the spot test can be used in diagnosis of the acute nitrate poisoning to detect the methemoglobin existence in blood in the field conditions and we think that successful results can be obtained with methylene blue and vitamin C treatment in goats ingested nitrate fertilizer.
Keçilerde akut nitrat zehirlenmesi
Keywords: Nitrate poisoning; Goat